LIM Protein Ajuba Participates in the Repression of the ATR-Mediated DNA Damage Response - Kalan, Sampada; Matveyenko, Anastasiya; Loayza, Diego (Frontiers in Genetics, 2013)
LIM proteins constitute a superfamily characterized by the presence of a LIM domain, known to be involved in protein-protein interactions. Our previous work has implicated members of the Zyxin family of LIM proteins, namely TRIP6 and LPP, in the repression of the DNA damage response at telomeres. Here, we describe a role for Ajuba, a closely related LIM molecule, in repressing the ATR-mediated DNA damage response. We found that depletion of Ajuba led to apparent delays in the cell cycle, accompanied with increased Rb phosphorylation, Chk1 phosphorylation, induction of p53 and cell death. Ajuba could be found in a complex with RPA, and its depletion led to RPA phosphorylation, known to be an early event in ATR activation. We propose that Ajuba protects against unscheduled ATR signaling by preventing inappropriate RPA phosphorylation.